Clinical experience with gamma knife stereotactic radiosurgery in the management of vestibular schwannomas secondary to type 2 neurofibromatosis. Issue 9 (21st August 2003) - Rowe, J G; Radatz, M W R; Walton, L; Soanes, T; Rodgers, J; Kemeny, A A
Abstract : Objective: To evaluate the results of stereotactic radiosurgery treating vestibular schwannomas secondary to type 2 neurofibromatosis. Methods: A retrospective review of 122 type 2 neurofibromatosis vestibular schwannomas consecutively treated in 96 patients. Tumour control was assessed by recourse to surgical intervention, by serial radiological imaging, and by the calculation of relative growth ratios in patients (n=29) habouring untreated contralateral tumours to act as internal controls. Hearing function was assessed with Gardner-Robertson grades and with averaged pure tone audiogram thresholds. Other complications are detailed. Results: Applying current techniques, eight years after radiosurgery it was estimated that 20% of patients will have undergone surgery for their tumour, 50% will have radiologically controlled tumours, and in 30% there will be some variable concern about tumour control, but up to that time they will have been managed conservatively. Relative growth ratios one and two years after treatment indicate that radiosurgery confers a significant (p=0.01) advantage over the natural history of the disease. Analysis of these ratios beyond two years was precluded by the need to intervene and radiosurgically treat the contralateral control tumours in more than 50% of the cases. This growth control was achieved with 40% of patients retaining their Gardner-Robertson hearing grades three years after treatment, (40% having some deterioration in grade, 20% becoming deaf). Pure tone audiogram results suggest some progressive long term hearing loss, although interpretation of this is difficult. Facial and trigeminal neuropathy occurred in 5% and 2%. Conclusions: Radiosurgery is a valuable minimally invasive alternative treatment for these tumours. For most patients, it controls growth or defers the need for surgery, or both. There is a price in terms of hearing function, although this may compare favourably with the deafness associated with the natural history of the disease, and with surgery. In deciding on therapy, patients should be aware of this treatment option.